Estrategias Metodológicas Para Incentivar El Pensamiento Científico En Estudiantes De Grado 3 Del Colegio Rufino Sur Sede Madre Marcelina (2012)
The development of the scientific thought, it is a fundamental tool in the development and acquisition of competitions, in addition it is a fundamental criterion in the limits curriculares for the area of natural Sciences, regulated by 115 General of Education and the new parameters of educational competitiveness. From the year 2000, the Educational Institution Rufino Jose Cuervo Sur of the city of Armenia, the pedagogic model of Education has helped for the Comprehension in order to look for an education based on competitions, but there were not applied methodological strategies that they were carrying to the acquisition of a significant learning in the area of Natural Sciences, in addition this one was not possessing a scientific character.